2005
DOI: 10.1093/gerona/60.9.1157
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Is Associated With an Increased Risk of Falls in Elderly Residents of a Long-Term Care Facility

Abstract: Our results suggest that diabetes mellitus is an independent fall risk factor among elderly nursing home residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
3
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(200 citation statements)
references
References 43 publications
9
182
3
6
Order By: Relevance
“…This difference demonstrated lower balance ability in patients with diabetic neuropathy according to balance indices, which is consistent with previous studies [1,[4][5][6]10,12,[14][15][22][23]. Aly et al reported significant differences between the stability indices (OSI, APSI, and LRSI) of control and diabetic neuropathy patients, with both open and closed eyes [1].…”
Section: Comparisons Of Groups Before Trainingsupporting
confidence: 90%
See 1 more Smart Citation
“…This difference demonstrated lower balance ability in patients with diabetic neuropathy according to balance indices, which is consistent with previous studies [1,[4][5][6]10,12,[14][15][22][23]. Aly et al reported significant differences between the stability indices (OSI, APSI, and LRSI) of control and diabetic neuropathy patients, with both open and closed eyes [1].…”
Section: Comparisons Of Groups Before Trainingsupporting
confidence: 90%
“…Diabetic neuropathy plays a significant role in falling among elderly patients [4]; people with peripheral neuropathy caused by diabetes often experience balance disorder [5]. Postural sway in these patients is increased, especially with the eyes closed [6].…”
Section: Introductionmentioning
confidence: 99%
“…This effect was more evident in people with diabetes and peripheral neuropathy possibly putting such patients at particular risk of falls. It is important that health care professionals recognise the potential for falls in those with DPN and implement early preventative strategies (25,26). M= Males, F= female, DM group = subjects with diabetes but no peripheral neuropathy and DPN group = subjects with diabetes and peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, a dismobilidade torna esses pacientes mais dependentes, conduz à perda de massa muscular e reduz a expectativa de vida (1). Os fatores predisponentes frequentes em portadores de diabetes incluem: neuropatia periférica, comprometimento visual, redução da função renal, alterações autonômicas e uso de medicamentos (2)(3)(4). Outras características presentes no paciente com DM2 são o sedentarismo e o ganho de peso (1) que, aliados à dismobilidade, têm como consequência o maior risco de quedas, que aparecem como importantes causas de ferimento não fatal entre pessoas com mais de 50 anos (5).…”
Section: Introductionunclassified